On the way to the web : the secret history of the internet and its founders - Banks, Michael A. (Apress, 2008)
"Was there an Internet before the Web? Who built it, and why? Do you want to know the real story behind the Internet? Are you curious as to who created all this stuff, and the business structure behind the online world? If so, you've come to the right place! Learn where, when, how and why the Internet came Into being, and exactly what hundreds of thousands of people were doing online before the Web. See who was behind it all, and what inspired them. The real stories are all here: the great businesses, colossal blunders, and great showmanship that led up to the Net and the Web-and beyond. turning your perception of the Web and the people who created it upside down."--Jacket